Ur in the twenty-first century CE - Rencontre assyriologique internationale (University Park, Pennsylvania)
xxxiii, 532 sayfa
Keywords: “Papers presented at the 62nd Rencontre Assyriologique Internationale, held in Philadelphia on July 11-15, 2016, examining archaeological, artistic, cultural, economic, historical, and textual matters related to the ancient city of Ur in southern Iraq“ --